A kind of cookware wear-resistant material and preparation method thereof

By using surface-modified dumbbell-shaped silicon carbide filler and porous silica-coated silver filler in the pot material, combined with polytetrafluoroethylene, methylphenyl silicone resin and antioxidant 1010, the problem of insufficient wear resistance and antibacterial performance of the pot material is solved, and the high performance and long-term effectiveness of the material are achieved.

CN119463594BActive Publication Date: 2025-04-25ZHEJIANG BAHE KITCHENWARE CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510048729.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-25
Estimated Expiration
2045-01-13

AI Technical Summary

Technical Problem

The existing pot materials have shortcomings in wear resistance and antibacterial properties, resulting in short service life and food safety and sanitary environments under high temperature, humid and complex environments.

Method used

Using a composite material, including surface-modified dumbbell-shaped silicon carbide filler and porous silica-coated silver filler, a coating with excellent wear resistance and antibacterial properties is formed through the synergy of polytetrafluoroethylene, methylphenyl silicone and antioxidant 1010.

Benefits of technology

It significantly improves the mechanical properties, interface bond strength and dispersion stability of the pot materials, extends the service life, and provides a long-lasting and safe antibacterial solution to meet the actual needs of high-performance pots.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463594B_ABST
    Figure CN119463594B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of cookware materials, and provides a cookware wear-resistant material and a preparation method thereof, wherein the material comprises the following components: surface modified dumbbell-shaped silicon carbide filler, porous silica-coated silver filler, polytetrafluoroethylene, methylphenyl silicone resin, antioxidant 1010, and deionized water. The dumbbell-shaped silicon carbide is prepared by ball milling, spray drying, sintering and hydrochloric acid treatment, and then modified by 3-aminopropyltriethoxysilane; the porous silica-coated silver filler is prepared by a sol-gel method using polystyrene latex as a template, and then prepared by reacting silver nitrate and ascorbic acid. The preparation method comprises the steps of dispersing, mixing, coating and curing, and the obtained material has excellent wear resistance and antibacterial properties, can be widely used in cookware surface coatings, and solves the problems of low wear resistance and poor antibacterial properties of traditional cookware materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of cookware materials, and in particular to a wear-resistant cookware material and a preparation method thereof. Background Art

[0002] With the rapid development of the modern kitchenware industry, consumers have put forward higher requirements for the performance of pots, especially in frequent use and complex cooking environments, the wear resistance and antibacterial properties of the pot surface are particularly important. In the process of long-term contact with high-temperature oil smoke, acidic and alkaline foods and metal cooking tools, the surface of the pot is often worn due to friction or chemical corrosion, resulting in the peeling of the functional coating and even the release of harmful substances, affecting the service life and food safety. In addition, the kitchen environment is humid and easy to breed bacteria. If the surface of the pot lacks antibacterial ability, it may become a medium for bacterial transmission, further threatening health. Therefore, the pot material needs to have not only excellent wear resistance to extend the service life, but also reliable antibacterial properties to ensure food safety and a hygienic environment. At the same time, the material must also show good chemical stability and environmental adaptability at high temperatures to ensure performance stability and safety in long-term use. Meeting these performance requirements can not only significantly improve the durability and hygiene of the pot, but also broaden its application scope in the high-end kitchenware market, and promote the industry to develop in a greener, safer and more efficient direction. Therefore, it is of great significance to develop cookware materials with both high wear resistance and antibacterial properties. This is not only a key technical direction to meet consumer needs, but will also become a core area of ​​competition in the future kitchenware industry.

[0003] At present, the development of cookware materials has made certain progress. For example, some materials use wear-resistant coatings or antibacterial coatings to improve performance, but the overall performance is still obviously insufficient. For example, the Chinese patent with publication number CN112773202A discloses a composite coating, which significantly improves the wear resistance by adding hard ceramics to the coating, but its antibacterial performance is poor and cannot meet the requirements of hygiene in the kitchen environment. In addition, the Chinese patent with publication number CN107981702B proposes an antibacterial coating material containing silver ion filler. Although it has good antibacterial properties, due to the weak wear resistance of its coating, the wear resistance in actual use is insufficient, affecting the service life of the coating. The main reason for these shortcomings is the lack of coordinated optimization of wear resistance and antibacterial performance in the existing material design. The improvement of a single performance is often at the expense of other performances. At the same time, the limitations of filler dispersion technology and coating process also lead to the failure to give full play to the material performance. Therefore, existing research urgently needs an innovative composite material that takes into account both wear resistance and antibacterial properties. Through scientific design of coating structure and filler optimization, the synergistic performance improvement can be achieved to meet the stringent requirements of modern kitchen utensils and promote further development of the industry. Summary of the invention

[0004] (1) Technical issues solved

[0005] The purpose of the present invention is to provide a cookware wear-resistant material and a preparation process to solve the problem that the current cookware wear-resistant material is insufficient in wear resistance and antibacterial performance.

[0006] (2) Technical solution

[0007] In order to achieve the above object, the present invention provides the following technical solutions:

[0008] A wear-resistant material for cookware, comprising the following components in parts by weight: 20.0-30.0 parts of surface-modified dumbbell-shaped silicon carbide filler, 5.0-10.0 parts of porous silica-coated silver filler, 30.0-40.0 parts of polytetrafluoroethylene, 10.0-20.0 parts of methylphenyl silicone resin, 0.1-0.5 parts of antioxidant 1010, and 6.0-10.0 parts of deionized water;

[0009] The cookware wear-resistant material is arranged on the surface of the cookware base;

[0010] The surface-modified dumbbell-shaped silicon carbide filler is obtained by surface-modifying the dumbbell-shaped silicon carbide with 3-aminopropyltriethoxysilane.

[0011] The preparation method of the surface modified dumbbell-shaped silicon carbide filler is as follows: 25 to 45 parts of dumbbell-shaped silicon carbide filler are placed in a beaker by weight, 3.0 to 5.0 wt.% of 3-aminopropyltriethoxysilane anhydrous ethanol solution is added at a stirring rate of 200 to 300 rpm for 60 to 120 minutes, and after the stirring is completed, the particles are collected by filtration, and then washed once with anhydrous ethanol. After the washing is completed, the particles are placed in a vacuum drying oven at 60 to 70° C. and dried for 180 to 240 minutes. After the drying is completed, the surface modified dumbbell-shaped silicon carbide filler is obtained.

[0012] The preparation method of the dumbbell-shaped silicon carbide is as follows: in parts by weight, carbon powder and silicon powder are placed in a ball mill in a mass ratio of 1: (1.25-1.5) in a ball mill, 2.0-5.0% magnesium oxide is added to the total mass of the powder, and then 2.0-4.0 times the total mass of the powder is added with anhydrous ethanol, followed by ball milling at a ball mill speed of 200-300 rpm for 240-360 minutes to form a uniform mixed slurry, and the obtained slurry is transferred to a spray dryer to form spherical particles with a particle size of 100-500 nm by spray drying. , the spherical particles are placed in an atmosphere tube furnace, sintered at 1200~1500℃ for 120~180min under argon atmosphere, and naturally cooled to room temperature after sintering. The cooled particles are placed in 100~150 parts of 10wt.% hydrochloric acid solution and stirred for 60~120min. After stirring, the solid powder is filtered and retained, and the solid powder is washed 3 times with deionized water. After washing, the solid powder is placed in an oven at 70~80℃ and dried for 240~300min. After drying, dumbbell-shaped silicon carbide is obtained.

[0013] Furthermore, the surface modified dumbbell-shaped silicon carbide filler has an average length of 240-360 nm and an average diameter of 120-220 nm.

[0014] The present invention adopts the design of surface-modified dumbbell-shaped silicon carbide filler mainly for enhancing the mechanical properties and interface bonding properties of the cookware wear-resistant material, while improving the dispersibility and processing adaptability of the material. By modifying the surface of dumbbell-shaped silicon carbide with 3-aminopropyltriethoxysilane, the surface active groups are given to it, which significantly enhances the interface interaction between the filler and the matrix material, thereby improving the mechanical properties and wear resistance of the material as a whole. The dumbbell-shaped silicon carbide has unique structural characteristics in morphological design. The spherical regions at both ends and the connecting part in the middle can form a stable physical mosaic structure inside the material. The uniqueness of this morphology not only improves the uniformity of the distribution of the filler in the matrix, but also significantly improves the efficiency of the transfer of the filler to the external force. In addition, the organosilicon group formed by the surface modification of 3-aminopropyltriethoxysilane can form a chemical bond with the organic components in the matrix, thereby improving the dispersion stability and interface bonding force of the filler in the matrix, thereby avoiding the adverse effects of the filler agglomeration phenomenon on the material performance. During the preparation process, the particle size and morphology of dumbbell-shaped silicon carbide were precisely controlled to give it an appropriate size distribution and surface properties, further optimizing its synergy with the matrix. In short, the dual synergy of surface-modified dumbbell-shaped silicon carbide filler in morphology design and surface modification enables it to provide excellent mechanical support in the material and improve the overall performance through interface effects, meeting the needs of high performance and high stability for cookware wear-resistant materials.

[0015] Furthermore, the preparation method of the porous silica-coated silver filler is as follows: by weight, 20 to 30 parts of porous silica hollow particles and 100 parts of deionized water are mixed and ultrasonically dispersed for 20 to 30 minutes, and then 5.0 to 8.0 parts of 0.15 mol / L silver nitrate solution are continuously added to the solution, and stirred at a stirring rate of 250 to 350 rpm for 90 to 150 minutes, and then the solution is filtered and the particles are collected, and then the collected particles are added to 100 parts of deionized water, and then the mixed solution is heated to 50 to 70° C., 2.0 to 5.0 parts of 0.15 mol / L ascorbic acid solution are slowly added dropwise, and stirring is continued for 30 to 90 minutes at a constant temperature, and then the solution is separated and the particles are retained, and the particles are washed with deionized water for 3 to 5 times. After washing, the particles are placed in a vacuum drying oven and dried at a temperature of 40 to 60° C. for 8 to 15 hours; after drying, a porous silica-coated silver filler is obtained.

[0016] Further, the preparation method of the porous hollow silica particles is as follows: in terms of weight fraction, tetraethyl orthosilicate is used as the silicon source, tetraethyl orthosilicate and anhydrous ethanol are placed in a beaker at a volume ratio of 1:(8-12), stirred at a stirring rate of 250-350 rpm, and stirred for 20-40 minutes until a uniform precursor solution is formed; then, 0.5-1.5% of the total mass of polystyrene latex particles are added to the solution, and the stirring rate is continued at 350-450 rpm, and stirred for 60-90 minutes, and then 20 ~30wt.% ammonia water, adjust the pH of the mixed solution to 8.5~11, and keep stirring for 90~150min. After the stirring is completed, let the solution stand for 10~14h, separate the formed particles by centrifugation and retain the precipitated particles, wash the precipitated particles with anhydrous ethanol for 3~5 times, and after the washing is completed, place the precipitated particles in an oven at 50~70℃ and dry for 5~8h; place the dried precipitated particles in a muffle furnace, and calcine at 500~600℃ for 180~300min. After the calcination is completed, cool to room temperature to obtain porous silica hollow particles.

[0017] Furthermore, the average diameter of the porous silica-coated silver filler is 200-500 nm, and the average diameter of the voids is 10-25 nm.

[0018] The present invention adopts the design of porous silica coated silver filler mainly for enhancing the antibacterial performance and wear resistance of cookware wear-resistant materials. By using porous silica as a carrier and coating silver particles on its surface, the filler is given excellent antibacterial properties and the slow release of silver ions is achieved. Porous silica is prepared by a sol-gel method, and its hollow core structure and uniform pore distribution provide a large specific surface area, so that silver particles can be evenly distributed on its surface and pores. This structural design not only effectively increases the silver loading, but also realizes the controlled release of silver ions through the restriction of pores, thereby prolonging the action time of antibacterial performance. In order to further enhance the antibacterial effect of the filler, silver nitrate is used as a silver source, and nano-scale silver particles are formed on the surface of porous silica by ascorbic acid reduction reaction. The controllable distribution of its particle size improves the antibacterial activity and avoids the adverse effects of silver particle agglomeration on performance. In addition, the hollow structure of porous silica has good lightness, can be evenly dispersed in the material, and achieve good physical intercalation and chemical compatibility with the matrix material, thus ensuring the stability and dispersibility of the filler in the composite material. The entire filler system achieves synergy through the high specific surface area, pore structure of porous silica and the antibacterial properties of silver particles, which not only enhances the antibacterial properties of the cookware material, but also ensures wear resistance, providing comprehensive antibacterial protection for the cookware material on the basis of wear resistance.

[0019] The present invention also provides a method for preparing the wear-resistant material for cookware, comprising the following steps:

[0020] S1. Dispersed filler: According to the ratio, add the surface modified dumbbell-shaped silicon carbide filler, porous silica-coated silver filler, polytetrafluoroethylene and deionized water into a high-speed mixer, disperse them at a stirring rate of 500-800 rpm for 20-30 min, and then ultrasonically disperse them in an ultrasonicator with a power of 200-300 W for 15-30 min to obtain a uniformly dispersed filler mixture.

[0021] S2. Matrix mixing: place methylphenyl silicone resin and antioxidant in a stirring container, and stir at a stirring rate of 300-500 rpm for 10-20 min to obtain a uniformly dispersed matrix solution.

[0022] S3. Overall mixing: gradually add the dispersed filler mixture into the base solution, stir at a rate of 300-500 rpm for 60-90 min to form a uniform coating material slurry.

[0023] S4. Coating construction and curing: The prepared coating material slurry is evenly applied to the surface of the pot by spraying, brushing or dipping, with a coating thickness of 15~30 , place the coated pot in a hot air drying oven at 50~70℃ to dry for 30~60min, then place the pot in an oven at 200~250℃ to cure for 30~60min. After curing, let the pot cool naturally to room temperature.

[0024] In order to further optimize the comprehensive performance of the material, polytetrafluoroethylene was selected as the matrix reinforcement material in the formula. Its excellent high temperature resistance and low friction coefficient provide the coating with better wear resistance and anti-adhesion properties. Methylphenyl silicone resin, as the matrix material, not only gives the coating good chemical stability and weather resistance, but also plays a bonding and stabilizing role when dispersing fillers. The addition of antioxidant 1010 effectively inhibits the oxidative degradation that may occur during high-temperature processing and use of the material, further extending the service life of the coating. Through reasonable component ratios and dispersion mixing processes, the components achieve synergistic effects in the material system, which not only enhances the mechanical properties and wear resistance of the coating, but also takes into account antibacterial properties and chemical stability, meeting the multiple performance requirements of cookware in high temperature, humid and complex environments, and providing a reliable technical solution for the high performance and multifunctionality of cookware materials.

[0025] (3) Beneficial technical effects

[0026] 1. The present invention significantly improves the mechanical properties, interface bonding strength and dispersion stability of the cookware wear-resistant material through the unique design of the surface-modified dumbbell-shaped silicon carbide filler. Compared with the prior art, its innovation is reflected in the dual optimization of morphology design and surface modification, which not only effectively solves the problems of filler agglomeration and insufficient interface bonding force in traditional wear-resistant materials, but also achieves comprehensive improvement in wear resistance, service life and processing adaptability. The special structure of the dumbbell-shaped silicon carbide significantly enhances the synergy between the filler and the matrix through physical intercalation and chemical bonding of 3-aminopropyltriethoxysilane, ensures a high degree of unity of mechanical properties and uniform distribution, and avoids performance degradation caused by stress concentration in traditional materials. The precise proportion of each component and the optimization of the preparation process further achieve the balance and improvement of the overall performance of the material, which has significant industry promotion value and provides an innovative solution for the long-term stability and high performance of cookware wear-resistant materials.

[0027] 2. The present invention significantly improves the antibacterial performance and wear resistance of the cookware wear-resistant material through the innovative design of porous silica-coated silver filler. Compared with the prior art, the high specific surface area and uniform pore structure of porous silica are used as carriers to achieve uniform distribution and slow release of silver particles, solving the problems of rapid attenuation of antibacterial effect and poor dispersion of fillers in traditional antibacterial materials. The nano-design of silver particles avoids agglomeration and further improves the antibacterial activity, while the lightweight properties of porous silica are well compatible with the matrix, ensuring the stability and processing adaptability of the filler. Through precise component ratios and optimized preparation processes, the components work synergistically, taking into account the balance between antibacterial performance and wear resistance, providing a long-term and safe antibacterial solution, which not only meets the actual needs of high-performance cookware, but also provides a new technical direction for the development of wear-resistant and antibacterial materials, and has broad application prospects and industry promotion value.

[0028] 3. The present invention significantly improves the wear resistance, anti-adhesion and chemical stability of the cookware coating through the synergistic effect of polytetrafluoroethylene, methylphenyl silicone resin and antioxidant 1010. Polytetrafluoroethylene provides low friction and high temperature tolerance, methylphenyl silicone resin enhances the dispersibility and weather resistance of the coating, and antioxidant 1010 effectively inhibits high temperature oxidative degradation and extends the life of the coating. The components achieve synergistic synergy through optimized ratios and dispersion processes, solving the problem of the difficulty in balancing wear resistance and chemical stability in the prior art, providing an innovative solution for the high performance of cookware materials, and has broad market prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a scanning electron microscope morphology image of the dumbbell-shaped silicon carbide prepared in Example 1 of the present invention.

[0030] Figure 2 This is the XRD phase analysis spectrum of the dumbbell-shaped silicon carbide prepared in Example 1 of the present invention.

[0031] Figure 3 This is a scanning electron microscope morphology image of the porous hollow silica particles prepared in Example 1 of the present invention.

[0032] Figure 4 This is the XRD phase analysis spectrum of the porous silica hollow particles prepared in Example 1 of the present invention.

[0033] Figure 5 This is a scanning electron microscope morphology image of the porous silica-coated silver filler prepared in Example 1 of the present invention.

[0034] Figure 6 This is the XRD phase analysis spectrum of the porous silica-coated silver filler prepared in Example 1 of the present invention.

[0035] Figure 7This is a scanning electron microscope morphology image of SiC used in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0036] To make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.

[0037] Example 1

[0038] A wear-resistant material for cookware comprises the following components in parts by weight: 20.0 parts of surface-modified dumbbell-shaped silicon carbide filler, 5.0 parts of porous silica-coated silver filler, 30.0 parts of polytetrafluoroethylene, 10.0 parts of methylphenyl silicone resin, 0.1 parts of antioxidant 1010, and 6.0 parts of deionized water.

[0039] The cookware wear-resistant material is arranged on the surface of the cookware base.

[0040] The surface-modified dumbbell-shaped silicon carbide filler of this embodiment is obtained by surface-modifying the dumbbell-shaped silicon carbide with 3-aminopropyltriethoxysilane.

[0041] The preparation method of the surface modified dumbbell-shaped silicon carbide filler of this embodiment is as follows: 25 parts of dumbbell-shaped silicon carbide filler are placed in a beaker by weight, 3.0 wt.% of 3-aminopropyltriethoxysilane anhydrous ethanol solution which is 1.0 times the mass of the dumbbell-shaped silicon carbide is added, and the mixture is stirred at a stirring rate of 200 rpm for 60 minutes. After the stirring is completed, the particles are collected by filtration, and then washed once with anhydrous ethanol. After the washing is completed, the particles are placed in a vacuum drying oven at 60° C. and dried for 180 minutes. After the drying is completed, the surface modified dumbbell-shaped silicon carbide filler is obtained.

[0042] The preparation method of the dumbbell-shaped silicon carbide of the present embodiment is as follows: in parts by weight, carbon powder and silicon powder are placed in a ball mill in a mass ratio of 1:1.25 in a ball mill, 2.0% magnesium oxide is added to the total mass of the powder, and then 2.0 times the mass of the total powder is added with anhydrous ethanol, followed by ball milling at a ball mill speed of 200 rpm for 240 minutes to form a uniform mixed slurry, the obtained slurry is transferred to a spray dryer to form spherical particles with a particle size of 100 nm by spray drying, the spherical particles are placed in an atmosphere tube furnace, sintered at 1200° C. for 120 minutes under an argon atmosphere, and naturally cooled to room temperature after sintering, the cooled particles are placed in 100 parts of 10wt.% hydrochloric acid solution and stirred for 60 minutes, after stirring, the solid powder is filtered and retained, the solid powder is washed 3 times with deionized water, after washing, the solid powder is placed in an oven at 70° C. and dried for 240 minutes, and dumbbell-shaped silicon carbide is obtained after drying.

[0043] The surface-modified dumbbell-shaped silicon carbide filler of this embodiment has an average length of 240 nm and an average diameter of 120 nm.

[0044] The preparation method of the porous silica-coated silver filler of the present embodiment is as follows: by weight, 20 parts of porous silica hollow particles and 100 parts of deionized water are mixed and ultrasonically dispersed for 20 minutes, and then 5.0 parts of 0.15 mol / L silver nitrate solution are continuously added to the solution, and stirred at a stirring rate of 250 rpm for 90 minutes, and then the solution is filtered and the particles are collected, and then the collected particles are added to 100 parts of deionized water, and then the mixed solution is heated to 50°C, and 2.0 parts of 0.15 mol / L ascorbic acid solution are slowly added dropwise, and the temperature is maintained and stirred for 30 minutes, and then the solution is separated and the particles are retained, and the particles are washed with deionized water for 3 times, and after washing, the particles are placed in a vacuum drying oven and dried at a temperature of 40°C for 8 hours; after drying, a porous silica-coated silver filler is obtained.

[0045] The preparation method of the porous silica hollow particles of the present embodiment is as follows: in terms of weight fraction, tetraethyl orthosilicate is used as the silicon source, and tetraethyl orthosilicate and anhydrous ethanol are placed in a beaker at a volume ratio of 1:8, and stirred at a stirring rate of 250 rpm for 20 minutes until a uniform precursor solution is formed; then, 0.5% of the total mass of polystyrene latex particles are added to the solution, and the stirring rate is continued to be 350 rpm, stirring for 60 minutes, and then 20wt.% ammonia water is slowly added to the solution, the pH of the mixed solution is adjusted to 8.5, and stirring is maintained for 90 minutes. After the stirring is completed, the solution is allowed to stand for 10 hours, the formed particles are separated by centrifugation and the precipitated particles are retained, and the precipitated particles are washed with anhydrous ethanol for 3 times. After the washing is completed, the precipitated particles are placed in a 50°C oven and dried for 5 hours; the dried precipitated particles are placed in a muffle furnace, and are heat-insulated and roasted at 500°C for 180 minutes. After the roasting is completed, they are cooled to room temperature to obtain porous silica hollow particles.

[0046] The average diameter of the porous silica-coated silver filler in this embodiment is 200 nm, and the average diameter of the voids is 10 nm.

[0047] A method for preparing a wear-resistant material for a cooker according to the present embodiment comprises the following steps:

[0048] S1. Dispersed filler: According to the ratio, the surface modified dumbbell-shaped silicon carbide filler, porous silica-coated silver filler, polytetrafluoroethylene and deionized water were added into a high-speed mixer, dispersed at a stirring rate of 500 rpm for 20 min, and then ultrasonically dispersed in an ultrasonicator with a power of 200 W for 15 min to obtain a uniformly dispersed filler mixture.

[0049] S2. Matrix mixing: Place methylphenyl silicone resin and antioxidant in a stirring container and stir at a stirring rate of 300 rpm for 10 min to obtain a uniformly dispersed matrix solution.

[0050] S3. Overall mixing: gradually add the dispersed filler mixture into the base solution, stir at a rate of 300 rpm for 60 min to form a uniform coating material slurry.

[0051] S4. Coating construction and curing: The prepared coating material slurry is evenly applied to the surface of the pot by spraying, with a coating thickness of 15 The coated pot is placed in a hot air drying oven at 50°C for 30 minutes, and then placed in an oven at 200°C for curing for 30 minutes. After curing, the pot is naturally cooled to room temperature.

[0052] pass Figures 1 to 6 The analysis results can clearly prove the preparation results and structural characteristics of Example 1 of the present invention. Figure 1 The scanning electron microscope morphology image shows the morphological characteristics of dumbbell-shaped silicon carbide, proving that it has a dumbbell-shaped structure; Figure 2 The XRD phase analysis spectrum further confirmed that the prepared product was SiC phase. Figure 3 The scanning electron microscope morphology image reveals the unique morphology of porous silica hollow particles, proving its porous hollow structure characteristics; Figure 4 The XRD phase analysis spectrum verifies that the material is a silicon dioxide phase. Figure 5 The SEM morphology shows that the silver particles are successfully encapsulated in the porous silica hollow core, proving the effectiveness of Ag encapsulation; Figure 6 The XRD phase spectrum further confirmed the existence of Ag and silica phases in the porous silica-coated silver filler. Figures 1 to 6 The characterization results together prove that the material prepared in Example 1 of the present invention has clear structural and phase characteristics.

[0053] Example 2

[0054] A wear-resistant material for cookware comprises the following components in parts by weight: 23.0 parts of surface-modified dumbbell-shaped silicon carbide filler, 6.5 parts of porous silica-coated silver filler, 33.0 parts of polytetrafluoroethylene, 13.0 parts of methylphenyl silicone resin, 0.2 parts of antioxidant 1010, and 7.2 parts of deionized water.

[0055] The cookware wear-resistant material is arranged on the surface of the cookware base.

[0056] The surface-modified dumbbell-shaped silicon carbide filler of this embodiment is obtained by surface-modifying the dumbbell-shaped silicon carbide with 3-aminopropyltriethoxysilane.

[0057] The preparation method of the surface modified dumbbell-shaped silicon carbide filler of this embodiment is as follows: 31 parts of dumbbell-shaped silicon carbide filler are placed in a beaker by weight, 3.6 wt.% of 3-aminopropyltriethoxysilane anhydrous ethanol solution which is 1.3 times the mass of the dumbbell-shaped silicon carbide is added, and the mixture is stirred at a stirring rate of 230 rpm for 78 minutes. After the stirring is completed, the particles are collected by filtration, and then washed once with anhydrous ethanol. After the washing is completed, the particles are placed in a vacuum drying oven at 63° C. and dried for 198 minutes. After the drying is completed, the surface modified dumbbell-shaped silicon carbide filler is obtained.

[0058] The preparation method of the dumbbell-shaped silicon carbide of the present embodiment is as follows: in parts by weight, carbon powder and silicon powder are placed in a ball mill in a mass ratio of 1:1.33 in a ball mill, 2.9% magnesium oxide is added with a total mass of the powder, and then anhydrous ethanol is added in an amount 2.6 times the mass of the total powder, followed by ball milling at a ball mill speed of 230 rpm for 276 minutes to form a uniform mixed slurry, the resulting slurry is transferred to a spray dryer to form spherical particles with a particle size of 220 nm by spray drying, the spherical particles are placed in an atmosphere tube furnace, sintered at 1290° C. for 138 minutes under an argon atmosphere, naturally cooled to room temperature after sintering, the cooled particles are placed in 115 parts of a 10wt.% hydrochloric acid solution and stirred for 78 minutes, filtered and retained the solid powder after stirring, the solid powder is washed 3 times with deionized water, and after washing, the solid powder is placed in an oven at 73° C. and dried for 258 minutes, and dumbbell-shaped silicon carbide is obtained after drying.

[0059] The surface-modified dumbbell-shaped silicon carbide filler of this embodiment has an average length of 276 nm and an average diameter of 142 nm.

[0060] The preparation method of the porous silica-coated silver filler of the present embodiment is as follows: by weight, 23 parts of porous silica hollow particles and 100 parts of deionized water are mixed and ultrasonically dispersed for 23 minutes, and then 5.9 parts of 0.15 mol / L silver nitrate solution are continuously added to the solution, and stirred for 108 minutes at a stirring rate of 280 rpm, and then the solution is filtered and the particles are collected, and then the collected particles are added to 100 parts of deionized water, and then the mixed solution is heated to 56° C., and 2.9 parts of 0.15 mol / L ascorbic acid solution are slowly added dropwise, and the temperature is maintained and stirred for 48 minutes, and then the solution is separated and the particles are retained, and washed with deionized water for 3 times. After washing, the particles are placed in a vacuum drying oven and dried at a temperature of 46° C. for 10 hours; after drying, a porous silica-coated silver filler is obtained.

[0061] The preparation method of the porous silica hollow particles of the present embodiment is as follows: in terms of weight fraction, tetraethyl orthosilicate is used as the silicon source, and tetraethyl orthosilicate and anhydrous ethanol are placed in a beaker at a volume ratio of 1:9.2, and stirred at a stirring rate of 280 rpm for 26 minutes until a uniform precursor solution is formed; then, 0.8% of the total mass of polystyrene latex particles are added to the solution, and the stirring rate is continued to be 380 rpm, and stirring is continued for 69 minutes, and then 23wt.% ammonia water is slowly added to the solution, the pH of the mixed solution is adjusted to 9.3, and stirring is maintained for 108 minutes. After the stirring is completed, the solution is allowed to stand for 11.2 hours, the formed particles are separated by centrifugation and the precipitated particles are retained, and the precipitated particles are washed with anhydrous ethanol for 3 times. After the washing is completed, the precipitated particles are placed in an oven at 56°C and dried for 5.9 hours; the dried precipitated particles are placed in a muffle furnace, and are kept and roasted at 530°C for 216 minutes. After the roasting is completed, they are cooled to room temperature to obtain porous silica hollow particles.

[0062] The average diameter of the porous silica-coated silver filler in this embodiment is 290 nm, and the average diameter of the voids is 12 nm.

[0063] A method for preparing a wear-resistant material for a cooker according to the present embodiment comprises the following steps:

[0064] S1. Dispersed filler: According to the ratio, the surface modified dumbbell-shaped silicon carbide filler, porous silica-coated silver filler, polytetrafluoroethylene and deionized water were added into a high-speed blender, dispersed at a stirring rate of 590 rpm for 23 min, and then ultrasonically dispersed in an ultrasonicator with a power of 230 W for 19 min to obtain a uniformly dispersed filler mixture.

[0065] S2. Matrix mixing: Place methylphenyl silicone resin and antioxidant in a stirring container and stir at a stirring rate of 360 rpm for 13 min to obtain a uniformly dispersed matrix solution.

[0066] S3. Overall mixing: gradually add the dispersed filler mixture into the base solution, stir at a rate of 360 rpm for 69 minutes to form a uniform coating material slurry.

[0067] S4. Coating construction and curing: The prepared coating material slurry is evenly applied to the surface of the pot by brushing, with a coating thickness of 19.5 The coated pot is placed in a hot air drying oven at 56°C for 39 minutes, and then placed in an oven at 215°C for curing for 39 minutes. After curing, the pot is naturally cooled to room temperature.

[0068] Example 3

[0069] A wear-resistant material for cookware comprises the following components in parts by weight: 26.0 parts of surface-modified dumbbell-shaped silicon carbide filler, 8.0 parts of porous silica-coated silver filler, 36.0 parts of polytetrafluoroethylene, 16.0 parts of methylphenyl silicone resin, 0.3 parts of antioxidant 1010, and 8.4 parts of deionized water.

[0070] The cookware wear-resistant material is arranged on the surface of the cookware base.

[0071] The surface-modified dumbbell-shaped silicon carbide filler of this embodiment is obtained by surface-modifying the dumbbell-shaped silicon carbide with 3-aminopropyltriethoxysilane.

[0072] The preparation method of the surface modified dumbbell-shaped silicon carbide filler of this embodiment is as follows: 37 parts of dumbbell-shaped silicon carbide filler are placed in a beaker by weight, 4.2 wt.% of 3-aminopropyltriethoxysilane anhydrous ethanol solution which is 1.6 times the mass of the dumbbell-shaped silicon carbide is added, and the mixture is stirred at a stirring rate of 260 rpm for 96 minutes. After the stirring is completed, the particles are collected by filtration, and then washed once with anhydrous ethanol. After the washing is completed, the particles are placed in a vacuum drying oven at 66° C. and dried for 216 minutes. After the drying is completed, the surface modified dumbbell-shaped silicon carbide filler is obtained.

[0073] The preparation method of the dumbbell-shaped silicon carbide of the present embodiment is as follows: in parts by weight, carbon powder and silicon powder are placed in a ball mill in a mass ratio of 1:1.4 in a ball mill, 3.8% magnesium oxide is added with a total mass of the powder, and then anhydrous ethanol is added in an amount 3.2 times the mass of the total powder, followed by ball milling at a ball mill speed of 260 rpm for 312 minutes to form a uniform mixed slurry, the resulting slurry is transferred to a spray dryer to form spherical particles with a particle size of 340 nm by spray drying, the spherical particles are placed in an atmosphere tube furnace, sintered at 1380° C. for 156 minutes under an argon atmosphere, naturally cooled to room temperature after sintering, the cooled particles are placed in 130 parts of 10wt.% hydrochloric acid solution and stirred for 96 minutes, filtered and retained the solid powder after stirring, the solid powder is washed 3 times with deionized water, and after washing, the solid powder is placed in an oven at 76° C. and dried for 276 minutes, and dumbbell-shaped silicon carbide is obtained after drying.

[0074] The surface-modified dumbbell-shaped silicon carbide filler of this embodiment has an average length of 312 nm and an average diameter of 164 nm.

[0075] The preparation method of the porous silica-coated silver filler in this embodiment is as follows: by weight, 26 parts of porous silica hollow particles and 100 parts of deionized water are mixed and ultrasonically dispersed for 26 minutes, and then 6.8 parts of 0.15 mol / L silver nitrate solution are continuously added to the solution, and stirred for 126 minutes at a stirring rate of 310 rpm, and then the solution is filtered and the particles are collected, and then the collected particles are added to 100 parts of deionized water, and then the mixed solution is heated to 62°C, and 3.8 parts of 0.15 mol / L ascorbic acid solution are slowly added dropwise, and stirring is continued for 66 minutes while maintaining a constant temperature, and then the solution is separated and the particles are retained, and the particles are washed with deionized water for 4 times. After washing, the particles are placed in a vacuum drying oven and dried at a temperature of 52°C for 12.2 hours; after drying, a porous silica-coated silver filler is obtained.

[0076] The preparation method of the porous silica hollow particles of the present embodiment is as follows: in terms of weight fraction, tetraethyl orthosilicate is used as the silicon source, and tetraethyl orthosilicate and anhydrous ethanol are placed in a beaker at a volume ratio of 1:10.4, and stirred at a stirring rate of 310 rpm for 32 minutes until a uniform precursor solution is formed; then, 1.1% of the total mass of polystyrene latex particles are added to the solution, and the stirring rate is continued to be 410 rpm, and stirring is continued for 78 minutes, and then 26wt.% ammonia water is slowly added to the solution, the pH of the mixed solution is adjusted to 10.0, and stirring is maintained for 126 minutes. After the stirring is completed, the solution is allowed to stand for 12.4 hours, the formed particles are separated by centrifugation and the precipitated particles are retained, and the precipitated particles are washed with anhydrous ethanol for 4 times. After the washing is completed, the precipitated particles are placed in a 62°C oven and dried for 6.8 hours; the dried precipitated particles are placed in a muffle furnace, and are heat-insulated and roasted at 560°C for 252 minutes. After the roasting is completed, they are cooled to room temperature to obtain porous silica hollow particles.

[0077] The average diameter of the porous silica-coated silver filler in this embodiment is 380 nm, and the average diameter of the voids is 18 nm.

[0078] A method for preparing a wear-resistant material for a cooker according to the present embodiment comprises the following steps:

[0079] S1. Dispersed filler: According to the ratio, the surface modified dumbbell-shaped silicon carbide filler, porous silica-coated silver filler, polytetrafluoroethylene and deionized water were added into a high-speed blender, dispersed at a stirring rate of 680 rpm for 26 min, and then ultrasonically dispersed in an ultrasonicator with a power of 260 W for 24 min to obtain a uniformly dispersed filler mixture.

[0080] S2. Matrix mixing: Place methylphenyl silicone resin and antioxidant in a stirring container and stir at a stirring rate of 420 rpm for 16 min to obtain a uniformly dispersed matrix solution.

[0081] S3. Overall mixing: gradually add the dispersed filler mixture into the base solution, stir at a rate of 420 rpm for 78 minutes to form a uniform coating material slurry.

[0082] S4. Coating construction and curing: The prepared coating material slurry is evenly applied to the surface of the pot by dipping, and the coating thickness is 24 The coated pot is placed in a hot air drying oven at 62°C for 48 minutes, and then placed in an oven at 230°C for curing for 48 minutes. After curing, the pot is naturally cooled to room temperature.

[0083] Example 4

[0084] A wear-resistant material for cookware comprises the following components in parts by weight: 30.0 parts of surface-modified dumbbell-shaped silicon carbide filler, 10.0 parts of porous silica-coated silver filler, 40.0 parts of polytetrafluoroethylene, 20.0 parts of methylphenyl silicone resin, 0.5 parts of antioxidant 1010, and 10.0 parts of deionized water.

[0085] The cookware wear-resistant material is arranged on the surface of the cookware base.

[0086] The surface-modified dumbbell-shaped silicon carbide filler of this embodiment is obtained by surface-modifying the dumbbell-shaped silicon carbide with 3-aminopropyltriethoxysilane.

[0087] The preparation method of the surface modified dumbbell-shaped silicon carbide filler of this embodiment is as follows: 45 parts of dumbbell-shaped silicon carbide filler are placed in a beaker by weight, 5.0 wt.% of 3-aminopropyltriethoxysilane anhydrous ethanol solution which is 2.0 times the mass of the dumbbell-shaped silicon carbide is added, and the mixture is stirred at a stirring rate of 300 rpm for 120 min. After the stirring is completed, the particles are collected by filtration, and then washed once with anhydrous ethanol. After the washing is completed, the particles are placed in a vacuum drying oven at 70° C. and dried for 240 min. After the drying is completed, the surface modified dumbbell-shaped silicon carbide filler is obtained.

[0088] The preparation method of the dumbbell-shaped silicon carbide of the present embodiment is as follows: in parts by weight, carbon powder and silicon powder are placed in a ball mill in a mass ratio of 1:1.5 in a ball mill, 5.0% magnesium oxide is added to the total mass of the powder, and then anhydrous ethanol is added in an amount 4.0 times the mass of the total powder, followed by ball milling for 360 minutes at a ball mill speed of 300 rpm to form a uniform mixed slurry, the obtained slurry is transferred to a spray dryer to form spherical particles with a particle size of 500 nm by spray drying, the spherical particles are placed in an atmosphere tube furnace, sintered at 1500° C. for 180 minutes under an argon atmosphere, and naturally cooled to room temperature after sintering, the cooled particles are placed in 150 parts of 10wt.% hydrochloric acid solution and stirred for 120 minutes, after stirring, the solid powder is filtered and retained, the solid powder is washed 3 times with deionized water, after washing, the solid powder is placed in an oven at 80° C. and dried for 300 minutes, and dumbbell-shaped silicon carbide is obtained after drying.

[0089] The surface modified filler of this embodiment has an average length of 360 nm and an average diameter of 220 nm.

[0090] The preparation method of the porous silica-coated silver filler of the present embodiment is as follows: by weight, 30 parts of porous silica hollow particles and 100 parts of deionized water are mixed and ultrasonically dispersed for 30 minutes, and then 8.0 parts of 0.15 mol / L silver nitrate solution are continuously added to the solution, and stirred for 150 minutes at a stirring rate of 350 rpm, and then the solution is filtered and the particles are collected, and then the collected particles are added to 100 parts of deionized water, and then the mixed solution is heated to 70°C, and 5.0 parts of 0.15 mol / L ascorbic acid solution are slowly added dropwise, and the temperature is maintained and stirred for 90 minutes, and then the solution is separated and the particles are retained, and the particles are washed with deionized water for 5 times. After washing, the particles are placed in a vacuum drying oven and dried at a temperature of 60°C for 15 hours; after drying, a porous silica-coated silver filler is obtained.

[0091] The preparation method of the porous silica hollow particles of the present embodiment is as follows: in terms of weight fraction, tetraethyl orthosilicate is used as the silicon source, and tetraethyl orthosilicate and anhydrous ethanol are placed in a beaker at a volume ratio of 1:12, and stirred at a stirring rate of 350 rpm for 40 minutes until a uniform precursor solution is formed; then, 1.5% of the total mass of polystyrene latex particles are added to the solution, and the stirring rate is continued to be 450 rpm, stirring for 90 minutes, and then 30 wt.% ammonia water is slowly added to the solution, the pH of the mixed solution is adjusted to 11, and stirring is continued for 150 minutes. After the stirring is completed, the solution is allowed to stand for 14 hours, the formed particles are separated by centrifugation and the precipitated particles are retained, and the precipitated particles are washed with anhydrous ethanol for 5 times. After the washing is completed, the precipitated particles are placed in a 70°C oven and dried for 8 hours; the dried precipitated particles are placed in a muffle furnace, and are heat-insulated and roasted at 600°C for 300 minutes. After the roasting is completed, they are cooled to room temperature to obtain porous silica hollow particles.

[0092] The average diameter of the porous silica-coated silver filler in this embodiment is 500 nm, and the average diameter of the voids is 25 nm.

[0093] A method for preparing a wear-resistant material for a cooker according to the present embodiment comprises the following steps:

[0094] S1. Dispersed filler: According to the ratio, the surface modified dumbbell-shaped silicon carbide filler, porous silica-coated silver filler, polytetrafluoroethylene and deionized water were added into a high-speed mixer, dispersed at a stirring rate of 800 rpm for 30 min, and then ultrasonically dispersed in an ultrasonicator with a power of 300 W for 30 min to obtain a uniformly dispersed filler mixture.

[0095] S2. Matrix mixing: Place methylphenyl silicone resin and antioxidant in a stirring container and stir at a stirring rate of 500 rpm for 20 min to obtain a uniformly dispersed matrix solution.

[0096] S3. Overall mixing: gradually add the dispersed filler mixture into the base solution, stir at a rate of 500 rpm for 90 minutes to form a uniform coating material slurry.

[0097] S4. Coating construction and curing: The prepared coating material slurry is evenly applied to the surface of the pot by spraying, with a coating thickness of 30 The coated pot is placed in a hot air drying oven at 70°C for 60 minutes, and then placed in an oven at 250°C for curing for 60 minutes. After curing, the pot is naturally cooled to room temperature.

[0098] Comparative Example 1

[0099] The same as Example 1, except that the cookware wear-resistant material is added with an equal amount of SiC particles, which are purchased from Hefei Kejing Material Technology Co., Ltd. Figure 7 As shown, its morphology is that of ordinary spherical particles, and its average diameter is close to the average diameter of dumbbell-shaped silicon carbide.

[0100] Comparative Example 2

[0101] It is basically the same as Example 1, except that the dumbbell-shaped silicon carbide is not subjected to surface modification treatment.

[0102] Comparative Example 3

[0103] The method is basically the same as Example 1, except that an equal amount of porous silica hollow core particles is used to replace the porous silica coated silver filler, so the filler is not coated with silver.

[0104] Performance Testing:

[0105] Wear resistance: The wear resistance of the PTFE composite coating was tested using a universal friction and wear tester (MFT-5000), with friction coefficient and wear rate as the main evaluation indicators. During the test, the motion mode was reciprocating linear motion, the test parameters were a loading force of 10N, a frequency of 1Hz, and a test time of 10 minutes, and the grinding material was a silicon nitride ceramic ball with a diameter of 9.525 mm. After the test, the wear marks left on the coating surface were placed on an MFP-D three-dimensional profiler for observation, the wear mark morphology was measured, and the wear amount was calculated, so as to obtain the wear rate W, in order to comprehensively evaluate the wear resistance of the PTFE composite coating.

[0106] Antibacterial property: The antibacterial property test of the wear-resistant material of the cookware includes two parts: quantitative analysis and qualitative analysis. In the quantitative analysis, Escherichia coli and Staphylococcus aureus were selected as the test bacteria. Liquid and solid culture media were prepared first, and the experimental equipment and sample membrane were sterilized by high temperature and high pressure. Then, the bacteria were activated and the concentration was prepared. The bacterial suspension was diluted to an appropriate concentration by ten-fold dilution method, inoculated into the culture medium, and added to the sample membrane for shaking culture for 8-10 hours. Then 100 Dilute the inoculum to to The range was coated on the surface of the agar medium, and the colony growth was observed and analyzed after incubation at 37°C for 24 hours. In the qualitative analysis, after the same treatment as the first five steps of the quantitative analysis, the bacterial solution was diluted and coated on the surface of the solid culture medium, and a sample film with a diameter of 2 cm was attached to the culture medium of different concentrations, and incubated at 37°C for 24 hours. The antibacterial effect was evaluated by observing the size of the inhibition zone. Finally, the inhibition rate was calculated by statistically comparing the number of colonies in the inoculated bacterial solution, and the antibacterial properties of the material were characterized in a quantitative manner.

[0107] The performances of the cookware wear-resistant materials of Examples 1 to 4 and Comparative Examples 1 to 3 are summarized in Table 1.

[0108] Table 1 Performance summary of wear-resistant materials for cookware in Examples 1 to 4 and Comparative Examples 1 to 3

[0109]

[0110] In Comparative Example 1, the coating material of the cookware is added with an equal amount of ordinary spherical SiC particles, and the dumbbell-shaped silicon carbide in the embodiment is not used. The morphology of such ordinary spherical SiC particles is relatively conventional, and their distribution and bonding force between fillers are not as good as dumbbell-shaped particles, resulting in poor wear resistance of the material. The test results show that the friction coefficient of the coating is 0.25 and the wear rate is , which are higher than those in the examples, showing higher friction resistance and greater wear volume. This shows that ordinary spherical SiC particles not only fail to significantly improve the wear resistance of the coating.

[0111] The main difference between Comparative Example 2 and the embodiment is that unmodified dumbbell-shaped silicon carbide particles are used. The unmodified dumbbell-shaped silicon carbide particles have low surface activity and poor compatibility with the coating substrate, resulting in a decrease in the wear resistance of the material. The test results show that the friction coefficient of the coating is 0.21 and the wear rate is , which are significantly higher than those in the examples, indicating that the wear resistance of the coating fails to maximize the advantages of the dumbbell-shaped silicon carbide.

[0112] The main difference between Comparative Example 3 and the Example is that porous silica hollow core particles without silver coating are used instead of porous silica coated silver fillers. Such fillers without silver coating have poor antibacterial properties, resulting in a significant decrease in the ability of the coating to inhibit bacteria. The test results show that the antibacterial rate against Escherichia coli is only 85.3%, and the antibacterial rate against Staphylococcus aureus is only 84.7%, which is much lower than the antibacterial rate of nearly 99% in the Example.

[0113] In summary, the main difference between the embodiment and the comparative example lies in the design and processing of key components. Dumbbell-shaped silicon carbide particles are used in the embodiment, and their special morphology helps to improve the distribution uniformity and structural stability of the coating; at the same time, the surface modification of the dumbbell-shaped silicon carbide further enhances its bonding with the matrix material. In addition, the porous silica-coated silver filler used in the embodiment not only provides the porous structure advantage of the material, but also imparts significant antibacterial properties through the introduction of silver. In the comparative example, ordinary spherical silicon carbide particles are unevenly distributed in the coating and have weak bonding due to morphological limitations, the unmodified dumbbell-shaped silicon carbide particles have poor compatibility, and the porous silica not coated with silver lacks effective antibacterial function. The differences in these components directly affect the comprehensive performance optimization of the material, making the embodiment more advantageous in material design.

[0114] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that all equivalent structural changes made under the concept of the present invention and using the contents of the present invention specification and drawings should be covered within the scope of protection of the claims of the present invention.

Claims

1. A wear-resistant material for cookware, characterized in that: The invention comprises the following components in parts by weight: 20.0-30.0 parts of surface modified dumbbell-shaped silicon carbide filler, 5.0-10.0 parts of porous silica-coated silver filler, 30.0-40.0 parts of polytetrafluoroethylene, 10.0-20.0 parts of methylphenyl silicone resin, 0.1-0.5 parts of antioxidant 1010, and 6.0-10.0 parts of deionized water; The cookware wear-resistant material is arranged on the surface of the cookware base; The surface-modified dumbbell-shaped silicon carbide filler is obtained by surface-modifying the dumbbell-shaped silicon carbide with 3-aminopropyltriethoxysilane; The preparation method of the dumbbell-shaped silicon carbide is as follows: in parts by weight, carbon powder and silicon powder are placed in a ball mill in a mass ratio of 1: (1.25-1.5) in a ball mill, 2.0-5.0% magnesium oxide is added to the total mass of the powder, and then 2.0-4.0 times the total mass of the powder is added with anhydrous ethanol, followed by ball milling at a ball mill speed of 200-300 rpm for 240-360 minutes to form a uniform mixed slurry, and the obtained slurry is transferred to a spray dryer to form spherical particles with a particle size of 100-500 nm by spray drying. , the spherical particles are placed in an atmosphere tube furnace, sintered at 1200~1500℃ for 120~180min under argon atmosphere, and naturally cooled to room temperature after sintering. The cooled particles are placed in 100~150 parts of 10wt.% hydrochloric acid solution and stirred for 60~120min. After stirring, the solid powder is filtered and retained, and the solid powder is washed 3 times with deionized water. After washing, the solid powder is placed in an oven at 70~80℃ and dried for 240~300min. After drying, dumbbell-shaped silicon carbide is obtained.

2. A wear-resistant material for cookware according to claim 1, characterized in that: The preparation method of the surface modified dumbbell-shaped silicon carbide filler is as follows: 25 to 45 parts of dumbbell-shaped silicon carbide filler are placed in a beaker by weight, 3.0 to 5.0 wt.% of 3-aminopropyltriethoxysilane anhydrous ethanol solution is added at a stirring rate of 200 to 300 rpm for 60 to 120 minutes, and after the stirring is completed, the particles are collected by filtration, and then washed once with anhydrous ethanol. After the washing is completed, the particles are placed in a vacuum drying oven at 60 to 70° C. and dried for 180 to 240 minutes. After the drying is completed, the surface modified dumbbell-shaped silicon carbide filler is obtained.

3. A wear-resistant material for cookware as claimed in claim 1 or 2, characterized in that: The surface modified dumbbell-shaped silicon carbide filler has an average length of 240-360 nm and an average diameter of 120-220 nm.

4. The wear-resistant material for cookware according to claim 1, characterized in that: The preparation method of the porous silica-coated silver filler is as follows: by weight, 20 to 30 parts of porous silica hollow particles and 100 parts of deionized water are mixed and ultrasonically dispersed for 20 to 30 minutes, and then 5.0 to 8.0 parts of 0.15 mol / L silver nitrate solution are continuously added to the solution, and stirred at a stirring rate of 250 to 350 rpm for 90 to 150 minutes, and then the solution is filtered and the particles are collected, and then the collected particles are added to 100 parts of deionized water, and then the mixed solution is heated to 50 to 70° C., 2.0 to 5.0 parts of 0.15 mol / L ascorbic acid solution are slowly added dropwise, and the temperature is maintained and stirred for 30 to 90 minutes, and then the solution is separated and the particles are retained, and the particles are washed with deionized water for 3 to 5 times, and after washing, the particles are placed in a vacuum drying oven and dried at a temperature of 40 to 60° C. for 8 to 15 hours; after drying, the porous silica-coated silver filler is obtained.

5. The wear-resistant material for cookware according to claim 1, characterized in that: The preparation method of the porous hollow silica particles is as follows: by weight, tetraethyl orthosilicate is used as a silicon source, and tetraethyl orthosilicate and anhydrous ethanol are placed in a beaker at a volume ratio of 1:(8-12), and stirred at a stirring rate of 250-350 rpm for 20-40 minutes until a uniform precursor solution is formed; then, 0.5-1.5% of the total mass of polystyrene latex particles are added to the solution, and the stirring rate is continued at 350-450 rpm, stirring for 60-90 min, then continue to slowly add 20-30wt.% ammonia water to the solution, adjust the pH of the mixed solution to 8.5-11, and keep stirring for 90-150 min. After the stirring is completed, the solution is allowed to stand for 10-14 h, the formed particles are separated by centrifugation and the precipitated particles are retained, the precipitated particles are washed with anhydrous ethanol for 3-5 times, and after the washing is completed, the precipitated particles are placed in an oven at 50-70°C to dry for 5-8 h; the dried precipitated particles are placed in a muffle furnace, and are heat-baked at 500-600°C for 180-300 min. After the calcination is completed, they are cooled to room temperature to obtain porous silica hollow particles.

6. A wear-resistant material for cookware as claimed in claim 1 or 4, characterized in that: The average diameter of the porous silica-coated silver filler is 200-500 nm, and the average diameter of the voids is 10-25 nm.

7. A method for preparing the wear-resistant material for cookware according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1. Dispersing fillers: According to the proportion, add the surface modified dumbbell-shaped silicon carbide filler, porous silica-coated silver filler, polytetrafluoroethylene and deionized water into a high-speed mixer, disperse them at a stirring rate of 500-800 rpm for 20-30 min, and then ultrasonically disperse them in an ultrasonicator with a power of 200-300 W for 15-30 min to obtain a uniformly dispersed filler mixture; S2. Matrix mixing: place methylphenyl silicone resin and antioxidant in a stirring container, and stir at a stirring rate of 300-500 rpm for 10-20 min to obtain a uniformly dispersed matrix solution; S3. Overall mixing: gradually add the dispersed filler mixture into the matrix solution, stir at a rate of 300-500 rpm for 60-90 min to form a uniform coating material slurry; S4. Coating construction and curing: The prepared coating material slurry is evenly applied to the surface of the cookware by spraying, brushing or dipping, with a coating thickness of 15-30 μm. The coated cookware is placed in a hot air drying oven at 50-70°C for 30-60 min, and then placed in an oven at 200-250°C for curing for 30-60 min. After curing, the cookware is naturally cooled to room temperature.

Citation Information

Patent Citations

  • Antibacterial non-stick cookware and manufacturing method thereof

    CN107981702B

  • Composite coating, preparation method thereof, cookware and cooking utensil

    CN112773202A

  • The Method for improving elastic modulus of particle reinforced aluminum-based composite material

    AU2020101927A4

  • Uniform heat-conducting non-stick pan coating and preparation method thereof

    CN113416474A